2022
DOI: 10.1007/s00586-022-07157-3
|View full text |Cite
|
Sign up to set email alerts
|

Georg schmorl prize of the German spine society (DWG) 2021: Spinal Instability Spondylodiscitis Score (SISS)—a novel classification system for spinal instability in spontaneous spondylodiscitis

Abstract: Purpose Even though spinal infections are associated with high mortality and morbidity, their therapy remains challenging due to a lack of established classification systems and widely accepted guidelines for surgical treatment. This study’s aim therefore was to propose a comprehensive classification system for spinal instability based on the Spinal Instability Neoplastic Score (SINS) aiding spine surgeons in choosing optimal treatment for spontaneous spondylodiscitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Evidence-based therapeutic concepts for infectious spondylodiscitis of the lumbar spine are still lacking (11). However, the latest publications discuss the rationale for using newly developed classification systems in improving the treatment of spondylodiscitis (12,13). CF-caused pyogenic spondylodiscitis is very rare, whereby reported cases predominantly occurred in high-risk patients, as did in our reported case, but contrary to our case, without previous instrumented lumbar fusion surgery (1-8).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Evidence-based therapeutic concepts for infectious spondylodiscitis of the lumbar spine are still lacking (11). However, the latest publications discuss the rationale for using newly developed classification systems in improving the treatment of spondylodiscitis (12,13). CF-caused pyogenic spondylodiscitis is very rare, whereby reported cases predominantly occurred in high-risk patients, as did in our reported case, but contrary to our case, without previous instrumented lumbar fusion surgery (1-8).…”
Section: Discussionmentioning
confidence: 56%
“…Evidence-based therapeutic concepts for infectious spondylodiscitis of the lumbar spine are still lacking ( 11 ). However, the latest publications discuss the rationale for using newly developed classification systems in improving the treatment of spondylodiscitis ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 The study by Schömig et al reported ICCs for interobserver reliability for the SINS and SISS as 0.961 and 0.960, respectively. 27 ICCs for the SITE Score were 0.989 (95% CI 0.975-0.997, p < 0.01) in the first round of validation, 0.992 (95% CI 0.981-0.998, p < 0.01) in the second round, and 0.961 (95% CI 0.929-0.980, p < 0.01) in the third round. Even though the patient cohorts for the SISS and the SITE Score were fundamentally different, our resulting ICCs support the high interrater reliability of our scoring system compared to alternate scoring systems like the SISS and clinically proven scoring systems like the SINS.…”
Section: Discussionmentioning
confidence: 92%
“…23 The resulting SINS system has become well established in the oncology spine surgeon community to help with decision-making for spinal neoplastic disease but unfortunately was not immediately transferable to spinal infections. 27 In response, Schömig et al published a variation of the SINS called the "Spinal Instability Spondylodiscitis Score" (SISS), 27 which determines insta-bility in spondylodiscitis cases. 28 The advantage of using the SISS appeared to be limited, as that scoring system resulted in a higher false-positive rate (unstable lesion with nonsurgical treatment) and lower false-negative rate (stable lesion with surgical treatment) than those associated with the SINS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation